Intention of Hospital Managers in Implementing the Balanced Scorecard - Aglita Janis Rupita S; Heru Kurnianto Tjahjono (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2018)
Achieving the implementation of a hospital's vision and mission depends on the strategies that used and the management of human resources. Balanced scorecard (BSC) is one of the strategic tools that are in great demand today to be applied in the health sector. The interest or intention in implementing of BSC depends on individual attitudinal factors, subjective norms and behavioral controls that refer to Planned Behavior (TPB). The aim of this study is to determine the intention of hospital managers in implementing the balanced scorecard. This type of research is quantitative descriptive with a cross sectional approach and the sampling technique used purposive sampling. The methods of data collecting used questionnaires, interviewed and analyzed by multiple linear regression. The results of the 90 samples showed an influence on attitudinal variables, subjective norms and simultaneous behavioral control as indicated by Sig = 0,000. While partially attitudinal variables (Sig = 0.029<0.05), subjective norm (Sig = 0.011<0.05) and behaviour control have effect on intention (Sig = 0.036<0.05).